Butterflies of Southwestern Bungo Range - Muhamad Ikhwan, Idris; Fatimah, Abang; Christharina, S Gintoron; Nur Azizuhamizah, Idris; Ahmad Irfan, Abdul Razak; Ratnawati, Hazali; Wan Nurainie, Wan Ismail; Raziman, Imam Ghazali; Mohamad Jalani, Mortada (UNIMAS Publisher, 2023)
Tropical rainforests are distinguished by the enormous biodiversity they support, within which, insects are the most diverse animal group. Spectacular insect groups such as the lepidopterans are among the best-known insects and serve as a good bioindicator group. An expedition to explore and document the diversity of butterflies in Bungo Range is essential as it is an important water catchment area that covers primary forest and secondary forest resulted from logging and agricultural activities years ago.